2010
DOI: 10.1517/14728220903512983
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CCL11 in the treatment of ovarian cancer

Abstract: Targeting CCL11 and its receptors through the use of monoclonal antibodies and small-molecule inhibitors may represent a beneficial new avenue of ovarian cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 82 publications
3
24
0
Order By: Relevance
“…To validate the elevation of CCL11 in clinical GBM tissues, it is necessary to clarify the source of CCL11. There are several studies suggesting that tumor cells themselves could be a possible source [8]. We found that cancer cells themselves could produce CCL11 and overexpress CCR3, indicating the activation of CCL11-CCR3 autocrine signaling in GBM.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…To validate the elevation of CCL11 in clinical GBM tissues, it is necessary to clarify the source of CCL11. There are several studies suggesting that tumor cells themselves could be a possible source [8]. We found that cancer cells themselves could produce CCL11 and overexpress CCR3, indicating the activation of CCL11-CCR3 autocrine signaling in GBM.…”
Section: Discussionmentioning
confidence: 53%
“…These effects are likely the result of multiple signaling pathways regulated by CCL11. Previous studies showed that the binding between CCL11 and CCR3 upregulated the expressions of VEGF, IL-8, PDGF-BB, and FGF [810]. In addition, it also induced phosphorylation of ERK1/2, MEK1 and STAT3 [5, 29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its role as a chemo-attractant, CCL11 has been implicated in different eosinophilic inflammatory diseases, such as atopic dermatitis, allergic rhinitis, sinusitis, asthma, ulcerative colitis, and in several other gastrointestinal disorders, as well as in parasitic infections [24][25][26][27][28]. Moreover, the levels of serum or plasma CCL11 as diagnostic or prognostic cancer markers have been described in high-grade renal cell carcinomas, high-risk neuroblastoma, as well as in head and neck small cell carcinomas [29][30][31].…”
Section: Discussionmentioning
confidence: 99%